Relationship between the Implementation of Discharge Planning and Recurrence of Hyperglycemia in DM Patients at the Pandan Regional General Hospital, Central Tapanuli Regency in 2020 - Selamat Ginting (Science Midwifery, 2022)
Diabetes mellitus (DM) is a metabolic disorder characterized by an increase in blood glucose levels due to interference with insulin action, or both. Hyperglycemia is the definition of a condition when blood glucose levels increase beyond normal limits. Discharge Planning is a process of interaction between multidisciplinary health workers, patients, and families who collaborate to provide and help nurse continuity that patients need. The purpose of this study was to determine the relationship between the implementation of discharge planning and recurrence of hyperglycemia in DM patients at the Pandan Regional General Hospital, Central Tapanuli Regency in 2020. The research sample was 55 respondents using simple random sampling technique. This type of research is quantitative with descriptive correlation method with cross sectional research design and data collected from respondents using a questionnaire sheet. The results of statistical tests carried out with a confidence level of 95% with = 0.05 obtained the value of p = 0.001, then p 0.001 <α (0.05). Or Ho is rejected, Ha is accepted, thus there is a relationship between the implementation of Discharge planning and recurrence of hyperglycemia in DM patients at the Pandan Regional General Hospital, Central Tapanuli Regency in 2020. Suggestions for the Pandan Regional General Hospital are expected to the Pandan Regional General Hospital for the results of this study. can be used as a reference in formulating nursing care planning in an effort to increase self-care knowledge and attitudes to DM clients.